PIDANA KERJA SOSIAL DALAM RANGKA MENCAPAI TUJUAN PEMIDANAAN DI INDONESIA - Yolanda Sari, Putu Astrid (Kertha Wicara : Journal Ilmu Hukum, 2013)
This paper entitled “COMMUNITY SERVICE ORDERS TO REACH THE SENTENCING PURPOSE”. This paper uses analytical methods and approaches normative comparisons. Community service orders is a new kind of criminal punishment in Indonesia which has purpose to foster and provide a deterrent effect for the offender by doing special patterns and concepts that are more humanis and give alot of beneficial not only for the offender but also for the community in order to achieve the purpose of sentencing in IndonesiaKey words: community service orders, sentencing purpose ,concepts, patterns.
Keywords: pidana kerja sosial, tujuan pemidanaan, konsep, pola.